Representing the Sandwich Generation in the Film 1 Kakak 7 Ponakan: A Roland Barthes Semiotic Analysis - Ikrimatul Amal; Suci Indah Sari; Analis Hasby (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2026)
The sandwich generation phenomenon, in which individuals are responsible for supporting multiple generations within the family simultaneously, has become an increasingly significant social issue due to its economic, emotional, and psychological consequences. Despite its growing prevalence, this phenomenon has received limited attention in studies examining its representation in film. This study aims to analyze how the sandwich generation is represented in the film 1 Kakak 7 Ponakan through Roland Barthes' semiotic framework. Employing a descriptive qualitative method within a post-positivist paradigm, the research analyzes selected scenes, dialogues, characters' expressions, settings, and visual symbols using Barthes' three levels of signification: denotation, connotation, and myth. The findings demonstrate that the film portrays the sandwich generation not only as a financial responsibility but also as a complex experience involving caregiving duties, personal sacrifice, emotional conflict, psychological pressure, and the tension between family obligations and individual aspirations. At the mythological level, the film reinforces the cultural belief that the eldest child or the family member perceived as the most capable bears a moral responsibility to prioritize family welfare over personal ambitions. These findings suggest that 1 Kakak 7 Ponakan functions not merely as a reflection of social reality but also as a medium that constructs and legitimizes cultural values of sacrifice, responsibility, and family solidarity, thereby contributing to broader discussions on family roles and the social meaning of the sandwich generation.